2020
DOI: 10.1186/s12954-019-0336-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating networked drug checking services in Toronto, Ontario: study protocol and rationale

Abstract: Background: The increasing incidence of fatal opioid overdose is a public health crisis in Canada. Given growing consensus that this crisis is related to the presence of highly potent opioid adulterants (e.g., fentanyl) in the unregulated drug supply, drug checking services (DCS) have emerged as part of a comprehensive approach to overdose prevention. In Canada's largest city, Toronto, a network of DCS launched in 2019 to prevent overdose and overdose-related risk behaviors. This network employs mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…These newer drug checking technologies are increasingly being included in public health responses to the current overdose epidemic, where fentanyl and other potent ingredients are linked to unprecedented numbers of overdose deaths [ 18 ]. The emerging responses are raising new questions [ 19 ]: Will people who inject alone, and face significant risk of overdose, access drug checking services [ 21 ]? What are the factors that influence people to access community drug checking, and how can emerging services be responsive to structural vulnerabilities [ 12 , 22 , 23 ]?…”
Section: Introductionmentioning
confidence: 99%
“…These newer drug checking technologies are increasingly being included in public health responses to the current overdose epidemic, where fentanyl and other potent ingredients are linked to unprecedented numbers of overdose deaths [ 18 ]. The emerging responses are raising new questions [ 19 ]: Will people who inject alone, and face significant risk of overdose, access drug checking services [ 21 ]? What are the factors that influence people to access community drug checking, and how can emerging services be responsive to structural vulnerabilities [ 12 , 22 , 23 ]?…”
Section: Introductionmentioning
confidence: 99%
“…It is within this context of fentanyl-related overdoses that drug checking has been re-emerging as a potential harm reduction intervention in Canada [6][7][8] and globally [9][10][11]. A 2017 evidence review of drug checking technologies and research concluded that communitywide drug checking may be instrumental as part of public health responses in British Columbia, and potentially a life-saving harm reduction service [12].…”
Section: Introductionmentioning
confidence: 99%
“…As of December 2020, there were nine SCS operating in Toronto. In response to the worsening overdose crisis, a range of harm reduction innovations emerged beyond SCS, notably a street drug-checking program [ 18 ] and “safer opioid supply (SOS)” programs. SOS are harm reduction programs aiming to reduce overdose risk by prescribing pharmaceutical opioids in place of unregulated street opioids [ 19 ].…”
Section: Introductionmentioning
confidence: 99%